Advancing Trans-Affirming Practice to Recognize, Account for, and Address the Unique Experiences and Needs of Transgender Sexual Assault Survivors. Issue 5 (September 2022) - Du Mont, Janice; Friedman Burley, Joseph; Hodgson, Robyn; Macdonald, Sheila
Transgender (trans) persons are sexually assaulted at high rates and often encounter barriers to equitable services and supports. The receipt of timely and appropriate postassault care, provided increasingly by specialized forensic nurses around the world, is critical in ameliorating the harms that accompany sexual assault. In order to adequately respond to the acute health care needs of trans clients and attend to longer term psychosocial difficulties that some experience, forensic nurses not only require specialized training but must also cultivate collaborative relationships with trans-positive health and social services in their communities. To meet this need, we describe our strategy to advance trans-affirming practice in the sexual assault context. We outline the design and evaluation of a trans-affirming care curriculum for forensic nurses. We also discuss the planning, formation, and maturation of an intersectoral network through which to disseminate our curriculum, foster collaboration, and promote trans-affirming practice across health care and social services in Ontario, Canada. Our approach to advancing trans-affirming practice holds the potential to address systemic barriers experienced by trans survivors and transform the response to sexual assault across other sectors and jurisdictions.